Synthesis of Transition-Metal–Boryl Complexes from Diboron Reagents - Zhang, Yifan; Chen, Yin Hei; Lyu, Hairong (Synthesis, 2025)
Transition metal (TM)-catalyzed borylation reactions using diboron reagents have been extensively studied and hold significant value in organic synthesis. As key intermediates in these reactions, TM–boryl complexes have garnered increasing research attention due to their crucial roles in catalytic processes. In this short review, we provide a comprehensive summary of diverse TM–boryl complexes synthesized from diboron reagents, highlighting their structures, reactivities, and roles in catalytic reactions. Additionally, future directions and perspectives for advancing this research field are discussed.
Keywords: TM–boryl complexes; Diboron reagents; Transition metal catalysis; Borylation; Organometallics